The impact of family environment on children’s anxiety level - Dudek, Mieczysław; Dolinská, Eva; Klein, Vladimir; Šilonová, Viera (Special Education, 2018)
Family and emotional relationships governing its functioning have a great influence upon the development of a person and his/her adult life. The specificity of a family environment is believed to be the key factor which either protects against, or contributes to, the emergence of developmental disorders during adolescence. Research results presented in this paper aim at highlighting the relationships between traits of family environment and children’s anxiety level. The research was conducted from 2015 to 2016 among 180 students of Polish junior high schools located in both: rural and urban areas.
Keywords: anxiety; family; upbringing